Identifikasi Kesalahan Mahasiswa Dalam Menyelesaikan Masalah Matematika (Studi Kasus Masalah Segitiga Pada Mata Kuliah Trigonometri) - Yayan Eryk Setiawan (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to describe mistakes made by first-semester students in solving triangle problems in trigonometry subjects. This research was a qualitative descriptive study with a case study approach. The subjects of this study were students of the first semester of the mathematics education study program at a tertiary institution in the city of Malang. The research instrument consisted of a question about solving triangular problems in the context of trigonometry and an interview guide. The data collected in this study consisted of the results of the subjects’ works and transcripts of interview results. Subject work data were analyzed descriptively to determine the type of error made by the subjects. The transcript data from the interview results were analyzed using coding which aimed to determine the factors causing the subjects’ errors. The results showed that the errors of 19 students in solving triangular problems in the context of trigonometry obtained 39% on concept errors, 28% on principle errors, 6% on miscalculations, and 33% on factual errors.